2005
DOI: 10.1007/s10616-005-5167-z
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Osteogenic Differentiation of Rat Periosteum-derived Cells

Abstract: Selection of appropriate cultures having an osteogenic potential is a necessity if cell/biomaterial interactions are studied in long-term cultures. Osteoblastic cells derived from rat long bones or calvaria have the disadvantage of being in an advanced differentiation stage which results in terminal differentiation within 21 days. In this regard, less differentiated periosteum-derived osteoprogenitors could be more suitable. Periosteum-derived cells were isolated from the tibiae of adult Wistar rats (n = 12). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Furthermore, culture expansion of PDC appears to be STAT3 dependent as inhibition of this pathway, either through interference with JAK2 or STAT3 directly, abrogates proliferation induced by serum growth factors [62]. While PDC do not overtly express osteogenic or chondrogenic properties during expansion, they can be induced to differentiate along the osteogenic, chondrogenic and adipogenic lineage in vitro by subjecting them to specific differentiation conditions, confirming their multipotent nature [44,57,60,61,63]. Evidence for the presence of genuine skeletal stem cells in the periosteum has been delivered by single-cell lineage analysis, showing that the periosteum contains cells with mesenchymal multipotency (osteogenic, chondrogenic, adipogenic and myogenic) at the clonal level [61].…”
Section: Isolation and Characterization Of Skeletal Progenitor Cells mentioning
confidence: 85%
See 1 more Smart Citation
“…Furthermore, culture expansion of PDC appears to be STAT3 dependent as inhibition of this pathway, either through interference with JAK2 or STAT3 directly, abrogates proliferation induced by serum growth factors [62]. While PDC do not overtly express osteogenic or chondrogenic properties during expansion, they can be induced to differentiate along the osteogenic, chondrogenic and adipogenic lineage in vitro by subjecting them to specific differentiation conditions, confirming their multipotent nature [44,57,60,61,63]. Evidence for the presence of genuine skeletal stem cells in the periosteum has been delivered by single-cell lineage analysis, showing that the periosteum contains cells with mesenchymal multipotency (osteogenic, chondrogenic, adipogenic and myogenic) at the clonal level [61].…”
Section: Isolation and Characterization Of Skeletal Progenitor Cells mentioning
confidence: 85%
“…For the isolation of animal PDC, either a similar technique is used or the periosteum is isolated by simply peeling off the periosteal layer from the bone. This method is particularly useful in young animals where the periosteal layer is relatively thick and only loosely attached to the bone [55][56][57][58][59]. In adult mice, the periosteum is only a few cell layers thick and thus difficult to isolate by dissection.…”
Section: Isolation and Characterization Of Skeletal Progenitor Cells mentioning
confidence: 99%
“…The observed shapes may be elongated, spindle‐shaped, triangular, or cuboidal. Some studies observed uniform morphology within the population, some are able to distinguish subpopulations of cells visually, and others report a more cuboidal or polyhedral morphology during early PDC progression along chondrogenic or osteogenic lineages [69, 86]. The morphology of PDCs also varies from species to species; for instance, rabbit‐derived PDCs are smaller than human PDCs under the same culture conditions [71].…”
Section: Defining the Pdcmentioning
confidence: 99%
“…Cell adhesion and proliferation on the scaffold not only define the biocompatibility of the scaffold but also its potential for in vivo applications. To simulate the cell growth characteristics, periosteum cells were isolated from rat tibial periosteum and expanded in culture, as shown in Figure A,B, following an earlier report Figure A shows the explant culture of the rat tibial periosteum, where cells can be observed to migrate from the explant to the tissue culture plate.…”
Section: Results and Discussionmentioning
confidence: 99%
“…To simulate the cell growth characteristics, periosteum cells were isolated from rat tibial periosteum and expanded in culture, as shown in Figure 3A,B, following an earlier report. 35 Figure 3A shows the explant culture of the rat tibial periosteum, where cells can be observed to migrate from the explant to the tissue culture plate. We first studied the migration of periosteal cells into the PUAOCC membrane.…”
Section: Intrinsic Antioxidant Activitymentioning
confidence: 99%